An integrative review of coping related to problematic computer use in adolescence - Trnka, Radek; Martínková, Zuzana; Tavel, Peter (International journal of public health, 2016)
OBJECTIVES: Problematic computer use is the use of computer technology that may be health-endangering and may cause immediate or later negative physical or psychological health outcomes or disturb well-being in users. The main purpose of this study was to review current empirical research on coping strategies which adolescents apply in the context of problematic computer use and the coping-relevant impacts of problematic computer use. METHODS: An integrative review of empirical studies using the Web of Science, Google Scholar, reference lists and forward tracking was conducted. Of the 404 articles identified, 28 peer-reviewed, full-text articles that directly addressed coping in relation to problematic Internet use, computer overuse and cyberbullying were included in the review. RESULTS: This review identified the structure of specific coping strategies related to problematic computer use as well as the general patterns of relationships between reviewed instances of problematic computer use, situational coping and dispositional coping. CONCLUSIONS: Instrumental action and talking with others were the most frequent strategies used by adolescents to cope with cyberbullying. The structure of the coping strategies related to problematic Internet use and computer overuse is highly differentiated, revealing a new and promising area for future research.
Keywords: Adolescent Behavior; Coping; Adaptation, Psychological; internet; Resilience; Adolescents; Adolescent; psychický stres; adaptace psychologická; Internet; mladiství; lidé; Adolescence; Humans; Computer use; Stress, Psychological; Bullying; šikana; chování mladistvých